Modeling and simulation of metallurgical processes: flotation, filtration, leaching and thickening - Lovera, Daniel (2005)
Over the last years, using phenomena models in interpreting and designing of software in metallurgical processes has been increasing. In this present research, a series of experimental test with polymetallic minerals is shown, which have been submitted to Flotation, Filtration, Leaching and Sedimentation processes. Mathematic modelling of such processes is shown, as well as the processing and simulation of the experimental data through the respective models. It is intended to contrast them with data from metallurgical plants for their respective validations. All these results will be used for a better planning and control of industrial variables in a concentrating plant.